Insights into the biodegradation of pentachlorobiphenyl by Microbacterium paraoxydans: proteomic and metabolomic studies - Ji, Lei; Chang, Xiaoyu; Wang, Leilei; Fu, Xiaowen; Lai, Wenkai; Zheng, Liwen; Li, Qi; Xing, Yingna; Yang, Zhongfeng; Guan, Yuyao; Yang, Fenglong (Frontiers in Microbiology, 2024)
Bacterial degradation mechanism for high chlorinated pentachlorobiphenyl (PentaCB) with worse biodegradability has not been fully elucidated, which could limit the full remediation of environments afflicted by the complex pollution of polychlorinated biphenyls (PCBs). In this research, a new PentaCB-degrading bacterium Microbacterium paraoxydans that has not been reported was obtained using enzymatic screening method. The characteristics of its intracellular enzymes, proteome and metabolome variation during PentaCB degradation were investigated systematically compared to non-PentaCB conditions. The findings indicate that the degradation rate of PentaCB (1 mg/L) could reach 23.9% within 4 hours and achieve complete degradation within 12 hours, with the mixture of intracellular enzymes being most effective at a pH of 6.0. During the biodegradation of PentaCB, the 12 up-regulated proteins characterized included ABC transporter PentaCB-binding protein, translocase protein TatA, and signal peptidase I (SPase I), indicating the presence of functional proteins for PentaCB degradation in both the cytoplasm and the outer surface of the cytoplasmic membrane. Furthermore, five differentially enriched metabolites were strongly associated with the aforementioned proteins, especially the up-regulated 1, 2, 4-benzenetriol which feeds into multiple degradation pathways of benzoate, chlorocyclohexane, chlorobenzene and aminobenzoate. These relevant results help to understand and speculate the complex mechanisms regarding PentaCB degradation by M. paraoxydans, which have both theoretical and practical implications for PCB bioremediation.